Homotaurine and Curcumin Analogues as Potential Anti-Amyloidogenic Agents - Jose Paredes Quiroz; Andi Zeng; Michelle Young; Patrick Gordon; Aadya Jaipuria; Kristi J. Reed; Greg M. Landry; Suhui Yang; Shreya Asher; Sabrina Ruoyao Chen Zhang; Ronny Priefer (Chemistry, 2023)
Currently, there is neither a cure for Alzheimer’s disease (AD) nor a way to stop the progressive death of neuronal cells associated with this devastating aliment. To date, there are only medications that temporarily slow its progression, and do not interfere with its pathogenesis. One of the hallmarks of AD is the presence of amyloid-beta plaques derived from the metabolism of the amyloid precursor protein, via the cleavage by beta followed by gamma secretase. Homotaurine, a naturally occurring small molecule found in some seaweeds, and curcumin, a phenolic antioxidant found in Curcuma longa, have been extensively studied as potential compounds to prevent/reverse plaque formation. In this study, libraries of chalcones and extended chalcones based on curcumin, as well as aminopropylsulfonamides inspired by homotaurine, were synthesized. Using fluorescence spectroscopic analysis with Thioflavin T, the anti-aggregation effect on Aβ42 was determined. A select number of newly synthesized chalcones and extended chalcone analogs were revealed to be potential anti-amyloidogenic agents. These were further evaluated with regard to their neurotoxicity/neuroprotection. The extended chalcone analogs that displayed the most anti-aggregation effect on Aβ42 were further analyzed in an MTT assay. Although none of the compounds alone displayed any neurotoxicity, none were able to provide neuroprotection against Aβ42.